Pattern Recognition in Bioinformatics Third IAPR International Conference, PRIB 2008, Melbourne, Australia, October 15-17, 2008. Proceedings - Chetty, Madhu; Ngom, Alioune; Ahmad, Shandar (Lecture Notes in Bioinformatics,, 2008)
This book constitutes the refereed proceedings of the International Workshop on Pattern Recognition in Bioinformatics, PRIB 2008, held in Melbourne, Australia, in October 2008. The 39 revised full papers presented were carefully reviewed and selected from 121 submissions. The papers discuss the applications of pattern recognition methods in the field of bioinformatics to solve problems in life sciences. The papers are organized in 6 topical parts on protein: structure, function and interaction; learning, classification and clustering; bio-molecular networks and pathways analysis; microarray and gene expression analysis; data mining and knowledge discovery; applications of high performance computing.